2023
DOI: 10.1001/jamaophthalmol.2023.2557
|View full text |Cite
|
Sign up to set email alerts
|

Association of Risk Variants in the CFH Gene With Elevated Levels of Coagulation and Complement Factors in Idiopathic Multifocal Choroiditis

Abstract: ImportanceIdiopathic multifocal choroiditis (MFC) is poorly understood, thereby hindering optimal treatment and monitoring of patients.ObjectiveTo identify the genes and pathways associated with idiopathic MFC.Design, Setting, and ParticipantsThis was a case-control genome-wide association study (GWAS) and protein study of blood plasma samples conducted from March 2006 to February 2022. This was a multicenter study involving 6 Dutch universities. Participants were grouped into 2 cohorts: cohort 1 consisted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Genetic variants in chromosome 1 lead to an increased risk of developing age-related macular degeneration driven predominantly by dysregulation of the complement system and are also associated with central serous chorioretinopathy and multifocal choroiditis. 27 , 34 , 35 CFH -rs1065489 polymorphism was associated with anterior uveitis, as well as uveitis recurrence. 36 There are many genetic variants or polymorphisms of the CFH gene in the general population; therefore, it would be interesting for future research to investigate whether these polymorphisms in the CFH gene are associated with retinal vascular involvement in idiopathic pediatric uveitis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Genetic variants in chromosome 1 lead to an increased risk of developing age-related macular degeneration driven predominantly by dysregulation of the complement system and are also associated with central serous chorioretinopathy and multifocal choroiditis. 27 , 34 , 35 CFH -rs1065489 polymorphism was associated with anterior uveitis, as well as uveitis recurrence. 36 There are many genetic variants or polymorphisms of the CFH gene in the general population; therefore, it would be interesting for future research to investigate whether these polymorphisms in the CFH gene are associated with retinal vascular involvement in idiopathic pediatric uveitis.…”
Section: Discussionmentioning
confidence: 93%
“… 25 Similarly, in adult patients with intermediate uveitis, elevated levels of complement cascade effectors and the coagulation system have been reported. 26 A recent study by de Groot et al 27 identified a key role of the complement and coagulation cascades in the underlying disease mechanisms of idiopathic multifocal choroiditis. Platelets are well known for their essential role in thrombus formation in response to vessel injuries.…”
Section: Discussionmentioning
confidence: 99%